2003
DOI: 10.1210/jc.2003-030570
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity of the Human Circadian Melatonin Rhythm to Resetting by Short Wavelength Light

Abstract: The endogenous circadian oscillator in mammals, situated in the suprachiasmatic nuclei, receives environmental photic input from specialized subsets of photoreceptive retinal ganglion cells. The human circadian pacemaker is exquisitely sensitive to ocular light exposure, even in some people who are otherwise totally blind. The magnitude of the resetting response to white light depends on the timing, intensity, duration, number and pattern of exposures. We report here that the circadian resetting response in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
491
1
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 677 publications
(530 citation statements)
references
References 0 publications
29
491
1
9
Order By: Relevance
“…These action spectra show distinct short wavelength sensitivity, identifying 457-464 nm as the most potent wavelength in suppressing nocturnal melatonin synthesis. Recent research also demonstrates that the ability of light to phase advance (Warman et al, 2003) and phase delay (Lockley et al, 2003) circadian rhythms shows a similar short wavelength sensitivity.…”
Section: Introductionmentioning
confidence: 94%
“…These action spectra show distinct short wavelength sensitivity, identifying 457-464 nm as the most potent wavelength in suppressing nocturnal melatonin synthesis. Recent research also demonstrates that the ability of light to phase advance (Warman et al, 2003) and phase delay (Lockley et al, 2003) circadian rhythms shows a similar short wavelength sensitivity.…”
Section: Introductionmentioning
confidence: 94%
“…This could be due to the ability of certain wavelengths of light to more effectively control circadian rhythms (Foster and Helfrich-Forster, 2001). Recent studies have found that light in the blue spectrum (446-477) outperforms other wavelengths in melatonin suppression, circadian phase shifting, and antidepressant effects (Brainard et al, 2001;Thapan et al, 2001;Lockley et al, 2003;Glickman et al, 2006). While there have been several studies that have investigated the mechanism by which light shifts the circadian clock and the specific photoreceptors involved in this effect (Foster and Helfrich-Forster, 2001;Foster et al, 2003), few studies have examined the effects of light-induced circadian phase shifting as an antidepressant in animal models.…”
Section: Bright Light Therapymentioning
confidence: 99%
“…In our study, light was not only in the low range of intensities (Zeitzer et al, 2005), but it was also shifted to the long wavelength range of the visible spectrum. It has been extensively shown that the circadian system is more sensitive to short wavelengths (Brainard et al, 2001;Cajochen et al, 2005;Lockley et al, 2003;Revell et al, 2005Revell et al, , 2006Thapan et al, 2001). Higher intensities of long wavelengths of light could have shifted the DLMO (Hanifin et al 2006;Zeitzer et al 1997), but they may also lead to undesired earlier wakefulness.…”
Section: Effects Of Artificial Dawn On Sleep Inertia 1233mentioning
confidence: 99%